Pengelolaan dan Pemanfaatan Sampah Plastik dengan Menggunakan Prinsip 3R di Madrasah Ibtidaiyah NU Sumput - Budi Prabowo; Sekar Mayang Qurrota A’yunin; Ayu Sukreni Hakim; Riski Famiyanti; Pingkan Syabila Tri Indiati (Jurnal Kabar Masyarakat, 2024)
Plastic waste management in educational environments is a significant challenge, especially in efforts to maintain environmental cleanliness and sustainability. This study aims to apply the 3R principle (Reduce, Reuse, Recycle) in the management and utilization of plastic waste at Madrasah Ibtidaiyah NU Sumput. Through a qualitative-descriptive approach, this study explores various strategies carried out by the madrasah in reducing plastic use, recycling plastic waste, and reusing plastic in daily activities. The results of the study indicate that the application of the 3R principle at Madrasah Ibtidaiyah NU Sumput has succeeded in significantly reducing the amount of plastic waste, increasing environmental awareness among students, and having a positive impact on the surrounding environment. This study concludes that the application of the 3R principle in plastic waste management in the school environment can be an effective model in supporting the educational environment and desires.